ANALISIS DAN PERANCANGAN SISTEM INFORMASI GEOGRAFIS LOKASI SEKOLAH DI KABUPATEN MUARO JAMBI - Cecilia, Cecilia; Sarjono, sarjono (Jurnal Manajemen Sistem Informasi, 2019)
The location of schools, especially Elementary School education in Muaro Jambi Regency, is currentlynot well known by outside communities or newcomers who have families and even communities in MuaroJambi Regency itself and it is also difficult to determine the location of the elementary school closest tothe house. This is due to the absence of realtime and factual information about Elementary Schools inMuaro Jambi District which made many people confused to find the location of the Elementary School.Therefore the author provides a solution in the form of designing a geographic information system for thelocation of an Android-based school. Where the expected results are in the form of a prototype that canlater be used to build a system that can provide information on the location of the school closest to hishome and school profile in real time and factual information